Dukungan Keluarga dan Resiliensi Akademik pada Mahasiswa di Universitas Klabat - Sanger, Ailine Yoan; Sigar, Dira (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
Academic resilience is the ability of students to withstand academic pressure. One of the factors that can influence academic resilience is family support. The purpose of this research is to determine the relationship between family support and academic resilience among nursing students at Klabat University. The method used is cross-sectional, with Pearson correlation statistical testing. This research uses purposive sampling techniques with Slovin's formula with a sample size of 109 respondents. The result showed that the majority of 39 (35.8%) respondents had moderate family support. Academic resilience was found to be predominantly at a moderate level with 49 (45.0%) respondents. The p-value result = 0.000 (< 0.05) with a correlation coefficient r = 0.600 indicates that there is a significant relationship between family support and academic resilience among nursing students at Klabat University, with a strong positive correlation. The higher the family support, the higher the resilience of the students will be. Recommendations are made for students to enhance their academic resilience by utilizing the support from their families, enabling them to be more resilient and persistent in facing academic challenges. Keywords: Academic resilience, family support, students